Acceptance and Use of Mobile Technology for Health Self-Monitoring in Lung Transplant Recipients during the First Year Post-Transplantation - Jiang, Yun; Sereika, Susan M.; DeVito Dabbs, Annette; Handler, Steven M.; Schlenk, Elizabeth A. (Applied Clinical Informatics, 2016)
To describe lung transplant recipients (LTRs’) acceptance and use of mobile technology for health self-monitoring during the first year post-transplantation, and explore correlates of the use of technology in the 0 to 2, >2 to ≤6, >6 to ≤12, and 0 to 12 months.Secondary analysis of data from 96 LTR assigned to use Pocket PATH®, a smartphone application, for daily health self-monitoring in a randomized controlled trial. Use of Pocket PATH was categorized as low, moderate, and high use. Proportional odds models for ordinal logistic regression were employed to explore correlates of use of technology.LTR reported high acceptance of Pocket PATH at baseline. However, acceptance was not associated with actual use over the 12 months (p=0.45∼0.96). Actual use decreased across time intervals (p<0.001). Increased self-care agency was associated with the increased odds of higher use in women (p=0.03) and those less satisfied with technology training (p=0.02) in the first 2 months. Higher use from >2 to ≤6 months was associated with greater satisfaction with technology training (OR=3.37, p=0.01) and shorter length of hospital stay (OR=0.98, p=0.02). Higher use from >6 to ≤12 months was associated with older age (OR=1.05, p=0.02), lower psychological distress (OR=0.43, p=0.02), and better physical functioning (OR=1.09, p=0.01). Higher use over 12 months was also associated with older age (OR=1.05, p=0.007), better physical functioning (OR=1.13, p=0.001), and greater satisfaction with technology training (OR=3.05, p=0.02).Correlates were different for short- and long-term use of mobile technology for health self-monitoring in the first year post-transplantation. It is important to follow up with LTR with longer hospital stay, poor physical functioning, and psychological distress, providing ongoing education to improve their long-term use of technology for health self-monitoring.Citation: Jiang Y, Sereika SM, DeVito Dabbs A, Handler SM, Schlenk EA. Acceptance and use of mobile technology for health self-monitoring in lung transplant recipients during the first year post-transplantation.
Keywords: Mobile applications; telemedicine; self-care; lung transplantation; patient compliance